2017
DOI: 10.1080/10641963.2017.1403621
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hyperhomocysteinemia and its associated factors in patients with primary hypertension in Chinese urban communities: A cross-sectional study from Nanjing

Abstract: Our present study reported a high prevalence of Hhcy in the Nanjing population with new-onset hypertension. Associated factors like physical activity, gender, smoking history, age, BMI, and LDL-c were important modifiers of plasma homocysteine concentration. Management and intervention of the above associated factors should be implicated to improve H type hypertension control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…It is also discussed debated whether the education level or BMI might have an influence on the risk of hyperhomocysteinemia. 20 21 Diet as a risk factor for hyperhomocysteinemia has been insufficiently studied. 22 Possible effects of smoking on the risk of developing hyperhomocysteinemia are also lacking.…”
Section: Introductionmentioning
confidence: 99%
“…It is also discussed debated whether the education level or BMI might have an influence on the risk of hyperhomocysteinemia. 20 21 Diet as a risk factor for hyperhomocysteinemia has been insufficiently studied. 22 Possible effects of smoking on the risk of developing hyperhomocysteinemia are also lacking.…”
Section: Introductionmentioning
confidence: 99%
“…There are sex and age differences in H-type hypertension, and the risk of H-type hypertension is higher in men than in women and increases with age (21,22). Similarly, we found that the risk of H-type hypertension in men was 7.879 times (OR=7.879), 1.73 times (OR=1.73), and 2.354 times (OR=2.354) higher than that in women in the healthy, HHcy, and hypertension populations, respectively, indicating that men were more likely to have hypertension with HHcy.…”
Section: ' Discussionmentioning
confidence: 99%
“…' INTRODUCTION H-type hypertension, a type of essential hypertension with hyperhomocysteinemia (HHcy), is a major risk factor of cardiovascular and cerebrovascular diseases, especially stroke (1)(2)(3). It has been reported that the risk of incident stroke is 12.7 times and that of stroke-related death is 11.7 times in patients with H-type hypertension compared with those in healthy controls (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…H-type hypertension (H-HTN) is a form of essential hypertension (HTN) often associated with hyperhomocysteinemia (HHCY) [ 1 ]. When human blood homocysteine level is above 15 μ mol/l, it is called hyperhomocysteinemia, and essential HTN accompanied by this sign is defined as H-HTN [ 2 ].…”
Section: Introductionmentioning
confidence: 99%